Development of Historical Calendar Media to Improve Students' Historical Thinking on World War I and II Material for Class XI SMA Negeri 1 Kabun - Yosi Anggela; Ahmal Ahmal; Bunari Bunari (Journal of Education Technology Information Social Sciences and Health, 2024)
SMAN 1 Kabun is one of the high schools in Kabun sub-district, Rokan Hulu Regency, Riau Province. At SMAN 1 Kabun, there are several students who still encounter problems in the learning process in the field, one of which is that when studying history, students listen more to explanations from teachers or educators. The learning resources used are printed books or packages and the use of learning media is less varied, during the learning process the teaching media used are books and projectors. So that students don't get bored quickly in learning and to improve students' historical thinking skills, researchers took the initiative to create a historical media calendar to improve students' thinking skills at SMA Negeri 1 Kabun. The research was carried out with the aim of developing the enthusiasm of students at SMAN 1 Kabun towards the subject. history by developing historical calendar learning media and conducting historical calendar feasibility tests for history learning at SMAN 1 Kabun, and seeing students' responses regarding historical calendar learning media. The research method used is the ADDIE development model. Based on research conducted, the historical calendar learning media was declared suitable for use in the teaching and learning process after analysis was carried out by material experts, media and students. The results of the validation of historical calendar learning media on World War I and II material by material experts obtained a total of 53 assessments while the percentage obtained was 96% in the very appropriate category, media experts with a total of 62 assessments while the percentage obtained was 88% in the very appropriate category, and the results of student respondents before using the media, the assessment given was 911 while the percentage obtained was 52% in the Fairly Good category. The results of student respondents learning using historical calendar media included a total of 1577 assessments, while the percentage obtained was 90% in the very good category. This research still experiences research limitations, where the research produced is still at a beginner level, so the researcher hopes that there will be research that can develop this historical calendar learning media so that it can be applied to other schools.